Neighbourhood income inequality and property crime. (January 2018) - Metz, Neil; Burdina, Mariya
This paper examines the relationship between income inequality and property crime using Census block group data from three US cities: Nashville, TN, Portland, OR and Tucson, AZ. This paper is one of very few to examine this relationship at such a fine geographic level, which is typically less than one square mile in size. We find that income inequality across block groups plays a key role in determining the level of property crime. As the income gap with one's poorest neighbouring block group widens, the level of property crime in the richer block group increases. Also, the poorest block group in an area tends to experience less property crime, holding all else constant.